Comparing Knowledge, Accessibility, and Use of Evidence-Based Chronic Disease Prevention Processes Across Four Countries - DeRuyter, Anna J.; Ying, Xiangji; Budd, Elizabeth L.; Furtado, Karishma; Reis, Rodrigo; Wang, Zhaoxin; Sung-Chan, Pauline; Armstrong, Rebecca; Pettman, Tahna; Becker, Leonardo; Mui, Tabitha; Shi, Jianwei; et al. (Frontiers in Public Health, 2018)
Abstract Background: Evidence-based chronic disease prevention (EBCDP) effectively reduces incidence rates of many chronic diseases, but many contextual factors influence the implementation of EBCDP worldwide. This study aims to compare knowledge, access, and use of chronic disease prevention processes across four countries. Methods: In this cross-sectional study, public health practitioners (N=400) from Australia (n121), Brazil (n=76), China (n=102), and the United States (n=101) completed a 26-question survey on EBCDP implementation. One-way ANOVA and Pearson’s Chi-Square tests were used to assess differences in contextual factors of interest by country. Results: Practitioners in China reported less knowledge of EBCDP processes (p<.001) and less use of repositories of evidence-based interventions than those from other countries (p<.001). Academic journals were the most frequently used method for accessing information about evidence-based interventions across countries. When selecting interventions, Brazilian and Chinese practitioners were more likely to consider implementation ease while the Australian and United States practitioners were more likely to consider effectiveness (p<.001). Conclusions: These findings can help inform within and across country strategies for improving the implementation of EBCDP.